Protective Effect of Osmundacetone against Neurological Cell Death Caused by Oxidative Glutamate Toxicity - Tuy An Trinh; Young Hye Seo; Sungyoul Choi; Jun Lee; Ki Sung Kang (Biomolecules, 2021)
Oxidative stress is one of the main causes of brain cell death in neurological disorders. The use of natural antioxidants to maintain redox homeostasis contributes to alleviating neurodegeneration. Glutamate is an excitatory neurotransmitter that plays a critical role in many brain functions. However, excessive glutamate release induces excitotoxicity and oxidative stress, leading to programmed cell death. Our study aimed to evaluate the effect of osmundacetone (OAC), isolated from Elsholtzia ciliata (Thunb.) Hylander, against glutamate-induced oxidative toxicity in HT22 hippocampal cells. The effect of OAC treatment on excess reactive oxygen species (ROS), intracellular calcium levels, chromatin condensation, apoptosis, and the expression level of oxidative stress-related proteins was evaluated. OAC showed a neuroprotective effect against glutamate toxicity at a concentration of 2 μM. By diminishing the accumulation of ROS, as well as stimulating the expression of heat shock protein 70 (HSP70) and heme oxygenase-1 (HO-1), OAC triggered the self-defense mechanism in neuronal cells. The anti-apoptotic effect of OAC was demonstrated through its inhibition of chromatin condensation, calcium accumulation, and reduction of apoptotic cells. OAC significantly suppressed the phosphorylation of mitogen-activated protein kinases (MAPKs), including c-Jun NH2-terminal kinase (JNK), extracellular signal-regulated kinase (ERK), and p38 kinases. Thus, OAC could be a potential agent for supportive treatment of neurodegenerative diseases.